Correction of proliferation and drug sensitivity defects in the progeroid Werner's Syndrome by Holliday junction resolution. - Rodriguez-Lopez, A; Whitby, M; Borer, C; Bachler, M; Cox, L (2007)
The progeroid Werner's syndrome (WS) represents the best current model of human aging. It is caused by loss of the WRN helicase/exonuclease, resulting in high levels of replication fork stalling and genomic instability. Current models suggest that characteristic WS phenotypes of poor S phase progression, low proliferative capacity, and drug hypersensitivity are the result of accumulation of alternative DNA structures at stalled or collapsed forks during DNA replication, and Holliday junction resolution has been shown to enhance survival of cis-platin-treated WS cells. Here, we present a direct test of the hypothesis that the replication/repair defect in unstressed WS cells is the result of an inability to resolve recombination intermediates. We have created isogenic WS cell lines expressing a nuclear-targeted bacterial Holliday junction endonuclease, RusA, and show that Holliday junction resolution by RusA restores DNA replication capacity in primary WS fibroblasts and enhances their proliferation. Furthermore, RusA expression rescues WS fibroblast hypersensitivity to replication fork blocking agents camptothecin and 4NQO, suggesting that the hypersensitivity is caused by inappropriate recombination at DNA structures formed when the replication fork arrests or collapses at 4NQO- or camptothecin-induced lesions. This work is the first to demonstrate that Holliday junction accumulation in primary Werner syndrome fibroblasts results in their poor proliferative capacity, and to rescue WS hypersensitivity to camptothecin and 4NQO by Holliday junction resolution.